Perceiving the void and the living being to build new environment friendly urban spaces - Scatena, Donatella (Journal of Architecture and Urbanism, 2018)
The definition of perception concerns the awareness of a reality considered external to the subject. Even before architecture and landscape, other disciplines had already dealt with perception.In psychology, simultaneously with the discovery of the unconscious by Freud and Jung, the Gestalt theory was developed, with which we passed from an elementary conception of perception to its definition as the sum of interrelated actions organised between themselves, moving the perceptive act on a purely inner level.German psychologist Kurt Zadek Lewin has shown that social behaviours are an expression of an exchange between the personal places of life and the environment. This theory was essential to deal with the phenomena of open spaces.In the perception of the landscape, the fragmented and partial view gets overcame by the holistic concept of environment, which allows us to conceive the landscape as a whole.The observer’s topic and its perception concern the centrality of the landscape concept, as it is defined by the European Landscape Convention. For architects, the observational notion takes on crucial importance both in the relationship between nature and artificial, both in relation to the context of the urban landscape and of the city open spaces. The analysis of Gordon Cullen and Kevin Lynch appears to be significant. Their researches on the subjective representation of the environment have shown how it is possible to distinguish between an objective and physical reality of the territory and the architectural space, and the perception of the singular environmental reality and of the personal space.In the ‘50s the duality of object-observed-outer and perception-inner of the subject was examined by the writer Aldus Huxley in The Doors of Perception, in which he described an outer landscape that gets reflected and amplified in the inner landscape. The works of the great landscape painters are born exactly from this marriage between inner and outer.In 1988 the aesthetic madness of Huxley found a scientific basis in the person of Gilles Deleuze, who attempted, through a metaphor, to define the evolution of perception and of the modern experience in the metaphysics of the chaos.And it is here that Deleuze, and with him Leibniz, returns to that perceiving the outside world as a reflection of the inner world.Nowadays the holistic concept of perception and the multiplicity of the gaze are studied and proposed by the science of geography and by a new sense of the places.